Seasonal and spatial variation of mesozooplankton biomass in ushuaia and golondrina bays (Beagle Channel, Argentina) - Biancalana, Florencia (2012)
The effects of a sewage effluent with no treatment on the mesozooplankton structure and the environmental quality were evaluated in the Bahía Blanca Estuary, during June to November 1995. The highest values of particulate organic matter, nutrients and specially phosphate, were observed in the effluent discharge zone. In addition, taxa richness, mesozooplankton abundance and Shannon diversity values were lower in the sewage discharge area compared with the less polluted area. Eurytemora americana and Acartia tonsa as well as larvae of Balanus glandula, Neohelice granulata and Spionidae were found in the discharge area with lower densities. These results highlight the importance of sewage effluent effects on mesozooplankton community providing background data to use in other monitoring programmes.